Using propensity scores to estimate effects of treatment initiation decisions: State of the science. (29th December 2020) - Webster‐Clark, Michael; Stürmer, Til; Wang, Tiansheng; Man, Kenneth; Marinac‐Dabic, Danica; Rothman, Kenneth J.; Ellis, Alan R.; Gokhale, Mugdha; Lunt, Mark; Girman, Cynthia; Glynn, Robert J.
Abstract: Confounding can cause substantial bias in nonexperimental studies that aim to estimate causal effects. Propensity score methods allow researchers to reduce bias from measured confounding by summarizing the distributions of many measured confounders in a single score based on the probability of receiving treatment. This score can then be used to mitigate imbalances in the distributions of these measured confounders between those who received the treatment of interest and those in the comparator population, resulting in less biased treatment effect estimates. This methodology was formalized by Rosenbaum and Rubin in 1983 and, since then, has been used increasingly often across a wide variety of scientific disciplines. In this review article, we provide an overview of propensity scores in the context of real‐world evidence generation with a focus on their use in the setting of single treatment decisions, that is, choosing between two therapeutic options. We describe five aspects of propensity score analysis: alignment with the potential outcomes framework, implications for study design, estimation procedures, implementation options, and reporting. We add context to these concepts by highlighting how the types of comparator used, the implementation method, and balance assessment techniques have changed over time. Finally, we discuss evolving applications of propensity scores.